Muhammed Ali : the world's champion - Tessitore, John. (New York : F. Watts, 1998)
A comprehensive biography of the only boxer crowned Heavyweight Champion of the World three times.
Includes bibliographical references (p. 132-136) and index.
Books for the Teen Age (NYPL).
School Library Journal.
Wilson's Junior High School.
Young Adult
Keywords: Ali, Muhammad, -- 1942- -- Juvenile literature; Ali, Muhammad, -- 1942-; Ali, Muhammad, -- 1942-; Boxers (Sports) -- United States -- Biography -- Juvenile literature; African Americans -- Biography; African Americans -- Biography; Boxers (Sports) -- Biography